Topics of dissertations in international affairs defended in Belarus in 1991–2021 - Huryn, Aliaksandr V. (Journal of the Belarusian State University. International Relations, 2024)
The author of the paper analyses topics of the international affairs dissertations defended in Belarus between 1991 and 2021 in the specialities “International law. European law”, “History of international relations and foreign policy”, “Politics of international relations, global and regional development”, and other related domains. Based on the number of dissertations and the range of topics covered, it is established that Belarus has developed a distinctive national school of international affairs scholarship since gaining its independence. After reviewing the successes and shortcomings field by field, it is concluded that historical research dominates the field, representing over 70 % of all international affairs dissertations defended. Increasing the number of doctors of science, post-doctoral and doctoral students, and defences, are identified as priorities for future development.
Keywords: international affairs studies; historiography of international relations; dissertation; international relations; foreign policy; international law; politics of international relations